Zhodnocení klinických výsledků operačně řešených akromioklavikulárních luxací typu Rockwood III se suturou či bez sutury korakoklavikulárního vazu - Hanus, Martin; Hudák, Radovan; Koníček, Petr; Šťastný, Eduard; Trč, Tomáš; Havlas, Vojtěch (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY Acromioclavicular (AC) joint dislocation and its surgical treatment still raises a number of questions that remain to be answered. In some types of dislocations, Rockwood type III in particular, the indication for surgical treatment as such is relative. There are numerous techniques and implants available for the reconstruction of AC joint. In our research we focused on the necessity of coracoclavicular (CC) joint reconstruction. MATERIAL AND METHODS In this paper, a cohort of 56 patients with Rockwood type III AC joint injury who underwent surgical treatment at our department in 2010-2016 period was retrospectively evaluated. The patients were treated with open reduction with AC joint stabilisation using hook plate or tension band. The patients were divided into 2 groups, namely group 1 with CC ligament reconstruction and group 2 without CC ligament reconstruction. The assessment was done at 6 months, 1 year and 2 years after surgery. The clinical outcomes were assessed based on the absolute Constant score (CS) and coracoclavicular distance (CCD) on the X-ray. Subsequently, the outcomes were statistically processed and compared using the Student s ttest. RESULTS The least invasive surgical intervention, as to the length of incision, was the reconstruction using the hook plate without CC ligament suture, whereas the longest incision was performed in tension band with CC ligament suture. In the CC ligament suture group, the mean operative time was 10 minutes longer. When evaluating the CS of the compared groups with and without CC ligament reconstruction, no statistically significant difference (p > 0.05) was found between the two groups. Similarly, the CCD values at 2-year follow-up did not show any statistically significant difference between the two groups (p > 0.05). CONCLUSIONS The available outcomes suggest that the surgical methods used by us are adequately safe and reliable. Good clinical outcomes can be achieved by open reduction and fixation of Rockwood type III AC joint dislocation even without CC ligament reconstruction. Key words: acromioclavicular dislocation, classification, reconstruction, coracoclavicular ligament.
Keywords: dislokace kloubu; sutura; Ligaments, Articular; Shoulder Dislocation; kloubní ligamenta; retrospektivní studie; Humans; výsledek terapie; lidé; luxace ramenního kloubu; Retrospective Studies; Treatment Outcome; Sutures; Joint Dislocations